The Transcription Factor Protein Sox11 Enhances Early Osteoblast Differentiation by Facilitating Proliferation and the Survival of Mesenchymal and Osteoblast Progenitors - Gadi, Jogeswar (American Society for Biochemistry and Molecular Biology, 2013)
Sox11 deletion mice are known to exhibit developmental defects of craniofacial skeletal malformations, asplenia, and hypoplasia of the lung, stomach, and pancreas. Despite the importance of Sox11 in the developing skeleton, the role of Sox11 in osteogenesis has not been studied yet. In this study, we identified that Sox11 is an important transcription factor for regulating the proliferation and survival of osteoblast precursor cells as well as the self-renewal potency of mesenchymal progenitor cells via up-regulation of Tead2. Furthermore, Sox11 also plays an important role in the segregation of functional osteoblast lineage progenitors from osteochondrogenic progenitors. Facilitation of osteoblast differentiation from mesenchymal cells was achieved by enhanced expression of the osteoblast lineage specific transcription factors Runx2 and Osterix. Morpholino-targeted disruption of Sox11 in zebrafish impaired organogenesis, including the bones, which were under mineralized. These results indicated that Sox11 plays a crucial role in the proliferation and survival of mesenchymal and osteoblast precursors by Tead2, and osteogenic differentiation by regulating Runx2 and Osterix.